Pelatihan Pengisian E-Form Spt Tahunan 1770 UMKM Untuk Relawan Pajak - Herti Diana Hutapea; Amran Manurung; Nancy Nopeline (Jurnal Visi Pengabdian Kepada Masyarakat, 2022)
The purpose of this community service is to provide training or technical guidance on how to fill out the 1770 SMEs Annual SPT E-Form for tax volunteers in 2022 so that tax volunteers can educate the public on the importance of taxes and assist taxpayers to report their taxes specifically filling out the SPT E-form. 1770 SMEs. This training was conducted online on Friday, February 11, 2022, 08.00-10.00 WIB, which was attended by 64 participants. The implementation of this event started from the opening, prayer and training, video screenings and question and answer sessions and participant feebacks. With this training, tax volunteers in 2022 can be trained in assisting SMEs taxpayers in educating the public about the importance of taxes, how to register NPWP, assisting taxpayers when they forget their passwords, in obtaining E-Fin and reporting the 1770 SMEs annual SPT with E-Form. And the existence of this training further equip tax volunteers in providing the best service to taxpayers, especially SMEs taxpayers. The implementation of this training still has technical problems because the training cannot be done in person because the process of implementing the training is online. However, based on feedback from the participants, even though there were technical obstacles, overall, the participants enthusiastically responded to every interaction with the speakers, they were able to clearly summarize the training carried out, so it can be concluded that the purpose of this service has been achieved.